Circular patterns of waste prevention and recovery - Ghisellini Patrizia; Santagata Remo; Zucaro Amalia; Ulgiat Sergio (E3S Web of Conferences, 2019)
The growth of modern societies with their scientific, economic and social achievements was made possible by the cheap availability of fossil fuels. Side effects of fossil energy resources were the development of unsustainable production and consumption patterns, the degradation of natural capital, and the release of airborne, waterborne and solid waste. Consumption and environmental loading are not only related to fuels, but also to other material resources, such as minerals in general and rare earths in particular. The increasing shortage of crucial resources affects and constrains important economic sectors (e.g., electronic sectors, renewable energies, food production), thus placing a limit on further development and wellbeing. Concepts of sustainable economies and communities, with focus on the social dimension of development and also on the ecological and economic aspects at the same time, are gaining the attention of policy makers, managers, and investors, as well as local stakeholders (organisations, small and medium enterprises, individual citizens) and encouraging new development and business models globally referred to as the “circular economy”. The circular economy (CE) is a production and consumption system that is restorative by intention and design. Although there has been a relative decoupling of economic growth from resource use in recent decades, the gains made so far have been eaten up by a combination of economic growth and the rebound effect. There are two questions: (i) why has it been so hard to move from theory(most often from rhetoric) to practice and implementation, and (ii) how is it possible to promote an innovative and effective CE strategy in urban systems where 60% of world population is concentrated. This shift (design, networking, organisation, implementation, community planning) and related monitoring tools constitute the skeletonof the transition that needs to occur within both urban systems and economies. The point we make is that a society without waste is not only desirable, but also possible and necessary. We cannot wait longer and we cannot just accept small adjustments, increased end-of-pipe technologies and the usual interplay of promises and conflicts. The time for a massive and successful effort towards a radical change of lifestyles and production/consumptionpatterns is now, where the term "waste" itself is considered a symptom of societal illness, an indicator of immature economies, poor science and old-fashioned technology.